Genetic and biomechanical factors in keratoconus: a review of pathogenic mechanisms, diagnostic strategies, and risk stratification - Pielak, Wiktoria; Koszewski , Jakub; Janiszewska, Anna; Kołkowski, Wiktor; Jakubczyk , Jan; Wądołowska, Monika; Antoszewska, Magdalena; Grabowska, Maria; Gozdera, Katarzyna; Oszast, Katarzyna (Quality in Sport, 2026)
Background. Keratoconus (KC) is a progressive, asymmetric corneal ectasia driven by inherited extracellular matrix variation that establishes a baseline biomechanical phenotype on which eye rubbing and atopy precipitate disease. Aim. To synthesize current evidence on the genetic architecture, the biomechanical phenotype, and the diagnostic strategies that integrate them. Materials and methods. A structured search of PubMed, Scopus, Web of Science, Google Scholar and bioRxiv covered primary research and meta-analyses on KC genetics, biomechanics, epidemiology, environmental risk, imaging and machine-learning diagnostics (1996–2026, plus selected earlier seminal papers). Results. Tomography-era prevalence reaches 1:375 in Northern European registries and over 1% in Scheimpflug-screened cohorts. GWAS implicates matrix-organizing loci (ZNF469, LOX, COL5A1, WNT10A) and corneal-thickness genes shared with Mendelian connective-tissue disease; a corneal-hysteresis GWAS bridges the genetic and biomechanical strands. In vivo metrics (corneal hysteresis, stress-strain index, Brillouin shift) and combined tomographic-biomechanical indices achieve AUCs above 0.99 for manifest disease and for detecting subclinical KC below the tomographic floor. Conclusions. Integrating genetic risk, biomechanical phenotyping and AI-based imaging enables earlier diagnosis, sharper risk stratification and better-timed cross-linking; multi-ancestry genetic studies and prospective biomechanical cohorts are research priorities.